The Representation of Muslim Women on Digital Platforms: Contestation and Fragmented Reception on Instagram’s QuranReview Account - Fawaid, Ahmad; Amalia, Nayla (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2025)
The representation of women in digital spaces has become a critical area of inquiry, as social media now serves not only as a medium for religious dissemination but also as a contested arena for discourse that shapes the social construction of Muslim communities. While previous studies have examined Qur’anic interpretations of women within academic and mainstream media contexts, limited attention has been paid to how these interpretations are constructed and publicly received on digital platforms—particularly Instagram, with its distinctive visual and interactive features. This study aims to analyze how the Instagram account @QuranReview represents Qur’anic interpretations related to women and to identify the patterns of public reception toward such content. Employing a qualitative descriptive approach and guided by reception theory, data were collected over a three-month period through the content analysis of 21 women-focused posts and 228 user comments, supplemented by non-participant observation. Thematic analysis using systematic coding procedures revealed a key finding: there has been a shift in interpretive authority from traditional scholars to digital figures who function as religious influencers in online spaces. This shift is accompanied by three dominant patterns of reception: progressive-affirmative, conservative-resistant, and critical-reflective. These findings underscore the urgency of re-evaluating the legitimacy of religious interpretation in the digital age and call for further studies that explore platform diversity and algorithmic influences in shaping public religious discourse.